Deciphering the function of YcbK lipoprotein-like hypo-thetical protein from Klebsiella pneumoniae MGH 78578. - Boon, Aun Teh; Choi, Sy Bing; Mohd Najimuddin, Mohd Nazalan; Salleh, Abu Bakar; A. Wahab, Habibah; Mohd Yahaya, Normi (2012)
Klebsiella pneumoniae is a Gram negative opportunistic pathogen which causes respiratory infection among immunocompromised patients. Recently more extended-spectrum beta-lactamase-producing K. pneumoniae strains are emerging worldwide making treatment for this bacterium more difficult. Approximately 20% of the genome of K. pneumoniae MGH 78578 encodes hypothetical proteins. Hypothetical proteins are proteins with unknown function where their sequences and structures are largely non-similar with other known proteins. Deciphering the functions of hypothetical proteins of this pathogen may give insight to possible new mechanisms leading to potential drug targets in the future. In this study, a particular lipoprotein-like hypothetical protein, YcbK, from K. pneumoniae MGH 78578 was cloned and characterized. Expression of YcbK in Escherichia coli JE5505 lipoprotein- deficient strain interestingly showed the presence of film-like material on the surface of the cells. In addition, the colonies on agar plates appeared to be smoother and more opaque than the negative control. Bioinformatics analysis on YcbK revealed it contains a putative conserved domain belonging to the Peptidase M15_3 superfamily. In silico homology modeling of the protein utilizing this conserved domain revealed that it preserves a Zn binding motif with two conserved His and Asp residues important for chelation of the metal ion. All the results obtained point to the possibility of YcbK adopting the function as a metallopeptidase with an important role in cell wall architecture similar with a few other peptidases in the family.